Pladu Tradition and Technocratic Regulation: Toward Collaborative Governance in Brantas River Dam Flushing Policy - Yudi Krisno Wicaksono; Dita Hendriani; Ivan Ashif Ardhana; Rizqi Bachtiar; Ima Frafika Sari (Khazanah Sosial, 2026)
This study analyzes the political sociology of power relations between technocratic state regulation and grassroots community autonomy in the context of the annual dam flushing policy along the Brantas River, East Java, Indonesia. Focusing on the traditional “Pladu” mass fish-catching practice, the research explores how riparian communities actively resist and negotiate centralized hydrological policies that prioritize infrastructure efficiency and securitization while marginalizing local socio-economic realities. Adopting a qualitative case study design, the researcher conducted non-participant observations during flushing events, semi-structured in-depth interviews with dam managers, government officials, village youth leaders, and fishermen, alongside analysis of official documents and digital community interactions. The data were examined through an interactive analytical model with triangulation for validity. The qualitative data were further quantified into intensity scales and visualized through thematic heatmap and network analysis using Python with Seaborn and NetworkX libraries. The findings reveal a profound contestation in which the state's rigid technocratic and securitized approach repeatedly fails to contain civil society's robust agency. Communities demonstrate sophisticated autonomy by decentralizing information via digital networks, self-organizing fishing zones, managing informal parking retribution for communal welfare, and implementing effective peer-based safety and conflict resolution mechanisms. These informal governance practices often prove more legitimate and functional than formal bureaucratic instruments, highlighting the erosion of state coercive authority at the local level and the emergence of an informal "shadow" social order. Drawing on Ansell and Gash's collaborative governance framework, the study argues that the long-dominant centralized technocratic paradigm has reached obsolescence. A genuine shift toward collaborative governance—through inclusive forums that integrate hydrological expertise with local social wisdom and recognize community sovereignty—offers a more equitable and sustainable resolution. Such a transition is essential to reconcile ecological infrastructure maintenance with the welfare rights of marginal workers, thereby advancing social justice in water resource governance.